Intravenous Immunoglobulin Therapy When Plasmapheresis Fails in Thrombotic Thrombocytopenic Purpura Associated with Severe ADAMTS 13 Deficiency in Childhood: A Case Report. (January 2013) - Pavone, P.; Passaniti, E.; Taibi, R.; Longo, M.R.; Nunnari, G.; Verrotti, A.; Serra, A.; Falsaperla, R.; Cocuzza, S.
Thrombotic thrombocytopenic purpura (TTP) is a disorder of the blood-coagulation system, causing extensive microscopic clots to form in the small blood vessels throughout the body. TTP is quite a rare pathology in childhood, being more frequent among adults. Often it is hardly to distinguish from other haematological pathologies in children both for its uncommon incidence and for the presence of clinical forms that are heterogeneous and difficult to classify. We report the case of an 11-year-old girl suffering from TTP, in whom the study of metallo-protease ADAMST 13 showed a low value (<10%) with positive anti-ADAMTS 13 Ig G and inhibitor, strengthening the hypothesis of autoimmune genesis. The girl was initially treated with cycles of plasmapheresis with both poor compliance and benefit for the girl and later treated with IV Immunoglobulin. This last treatment resulted in a rapid improvement of the symptomatology and no reappearance of the clinical signs at four-year follow-up.